Relationship between Time Interval from Admission to Delivery and Obstetrics Outcomes in Eclampsia/Severe Preeclampsia - Pandit, Upendra (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The purpose of this study was to find out the time interval from admission to delivery in eclamptic/ severe preeclamptic mothers and see the relationship to their obstetrics (maternal and fetal) outcomes. Methods: A retrospective case review was conducted at Nepalgunj Medical College, Teaching hospital, Nepalgunj. About 152 mothers with eclampsia/severe preeclampsia and postpartum eclampsia whom received either loading or both loading and maintenance doses of Magnesium Sulfate, while they were admitted to the hospital from 1stJanuary 2011 to 31st December 2015. Out of them, 132 were eclampsia/severe preeclampsia (antepartum / intrapartum) and 20 mothers were postpartum eclampsia were enrolled in the study. Descriptive analysis was used by reviewing medical records and Maternity registers. A 95% CI and P-value of <0.05 were considered as statistically significant. Results: Among 132 mothers, 53 (40.1%), 35 (26.5%) and 44 (33.3%) mothers delivered within 2 hours, 6 hours and ≥12 hours respectively. Ninety seven (73.4%) mothers underwent caesarean section, 27 (20.4%) had spontaneous vertex delivery 8(6%) underwent assisted vaginal deliveries. Out of 139 births there were 118 (84.8%) live births; 21 (15.1%) still births. The apgar score ≥7 at 5 minutes was seen in 81(58.2%) babies and low apgar <7 was seen in 37(26.6%) babies. and no evidence of live apgar "0" was seen in 23(16.5%).There were 2 neonatal deaths. Eleven still births in 2 hours, 4 in 6 hours and 6 in≥12 hours of admission were noted .Among 152 mothers including postpartum 20(13.1%) eclampsia, complications developed in 51 (33.5%) mothers. Maternal deaths were 2(1.3%). Conclusions: There is no significant difference in obstetrics outcomes in early (2 hour), later (6 hours) and late (≥12 hours) delivery of eclamptic/severe preeclamptic mothers.